VALIDATION OF DESIGNBUILDER SIMULATION ACCURACY USING FIELD MEASURED DATA OF INDOOR AIR TEMPERATURE IN A CLASSROOM BUILDING - Habu Yusuf Abba; Roshida Abdul Majid; Muhammad Hamdan Ahmed; Olutobi Gbenga Ayegbusi (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Studies have shown that a very wide range of parameters affect thermal comfort of building occupants. Heat transfer through the roofs has been identified as one of the causes of overheating in building interiors. Building Performance Simulation tools can be used to determine appropriate roof design parameters with optimum thermal performance in tropical climates like Nigeria. However, ensuring the reliability of the simulation results is essential for both occupants and designers. Therefore, this study seeks to verify and validate the accuracy of simulation results of DesignBuilder as a simulation tool for the present research works on roof thermal performance. The study primarily focuses on the impact of roof design on the air temperature in the indoor learning environment. Validation is examined by comparing the measured daily indoor air temperature of Kofar Wambai Secondary School Classroom, Bauchi city data and the simulation results. Comparative analysis indicate that the % deviation of field measured and simulated results for the tested days (18th and 21st September, 2018) were 2.39% and 1.25% respectively. The R2 results indicated 99% and 75% correlation between the simulated and measured indoor temperature on the tested days.These results agreed with the recommendations of a study by (Andelkovic et al, 2016) which reported that the marginal value of R2 for measurements and simulations validation is R2 â‰¥ 75%. Therefore, DesignBuilder can be employed to evaluate roof thermal performance as well as predict indoor air temperature of classroom buildings.